Violência autoprovocada entre adolescentes no Espírito Santo: uma análise dos casos notificados de 2011 a 2018 - Luis, Mayara Alves (2021)
Introduction: Adolescence is a life cycle in which greater independence and social contact begins. During this period, individuals can adopt risky behaviors when trying to seek new experiences and challenges, which facilitates relationships with peer groups and contributes to the development of autonomy, which may have negative consequences for development. Influenced by several factors, suicidal behavior and self-harm without suicidal intention are health problems that have a high magnitude among adolescents, and are risk factors for suicide. Objectives: To identify the frequency of self-harm in adolescents, reported in Espirito Santo from 2011 to 2018, and its association with the characteristics of the victim and the aggression. Method: cross-sectional analytical study. Data were obtained from reported data on self- inflicted and sexual violence against adolescents registered in the Information System for Diseases and Notification (SINAN) in Espirito Santo between 2011 and 2018. The dependent variable of the study was self-harm and the independent variables were age; race/color; disability/disorder; area of residence; place of occurrence; it happened other times; means of aggression and suspected alcohol consumption. Bivariate analyzes were performed using the Chi-Square (χ2) and Fisher's exact test. The multivariate analysis performed considered the log- binomial model and the adjustment results were presented in terms of the Prevalence Ratio. All analyzes were conducted using the statistical programs STATA 13.0 and R. Results: The prevalence of reported cases of self-harm was 33.0%, and of this total, 79.8% occurred among female adolescents. Regarding associations, there was a higher prevalence in adolescents aged 13 to 17 years (female) and 18 to 19 years (male) and among those with disabilities or disorder. Higher prevalence was found in residences and collective housing, as well as among those who did not consume alcohol at the event. In females there was also an association with the urban area (p<0.05). Conclusion: We emphasize the importance of actions to promote health, prevention and recovery among adolescents in order to reduce the occurrence of harm and possible other outcomes such as suicide.